A cyanide‐bridged heterometallic coordination polymer constructed from square‐planar [Ni(CN)4]2−: synthesis, crystal structure, thermal decomposition, electron paramagnetic resonance (EPR) spectrum and magnetic properties. Issue 7 (21st June 2016) - Qin, Ying-Lian; Yang, Bin-Wu; Wang, Gao-Feng; Sun, Hong
Abstract : The square‐planar [Ni(CN)4 ] 2− unit has been developed using O ‐donor ligands to form the coordination polymer [Cu II Ni II (CN)4 (H2 O)2 ]·H2 O, in which two‐dimensional layers are constructed by anionic [Ni(CN)4 ] 2− units that bridge to four adjacent cationic [Cu(H2 O)2 ] 2+ units through four μ2 ‐cyanide groups. A magnetic investigation showed the presence of a very weak antiferromagnetic interaction between the Cu II atoms through the diamagnetic [Ni(CN)4 ] 2− ion. Abstract : Square‐planar complexes are commonly formed by transition metal ions having a d 8 electron configuration. Planar cyanometallate anions have been used extensively as design elements in supramolecular coordination systems. In particular, square‐planar tetracyanometallate(II) ions, i.e. [ M (CN)4 ] 2− ( M II = Ni, Pd or Pt), are used as good building blocks for bimetallic Hofmann‐type assemblies and their analogues. Square‐planar tetracyanonickellate(II) complexes have been extensively developed with N ‐donor groups as additional co‐ligands, but studies of these systems using O ‐donor ligands are scarce. A new cyanide‐bridged Cu II –Ni II heterometallic compound, poly[[diaquatetra‐μ2 ‐cyanido‐κ 8 C : N ‐nickel(II)copper(II)] monohydrate], [Cu II Ni II (CN)4 (H2 O)2 ]·H2 O n, has been synthesized and characterized by X‐ray single‐crystal diffraction analyses, vibrational spectroscopy (FT–IR), thermal analysis, electron paramagnetic resonance (EPR) and magnetic moment measurements. The structural analysis revealed that it has a two‐dimensional grid‐like structure built up of cationic [Cu(H2 O)2 ] 2+ and anionic [Ni(CN)4 ] 2− units connected through bridging cyanide ligands. The overall three‐dimensional supramolecular network is expanded by a combination of interlayer O—H…N and intralayer O—H…O hydrogen‐bond interactions. The first decomposition reactions take place at 335 K under a static air atmosphere, which illustrates the existence of guest water molecules in the interlayer spaces. The electron paramagnetic resonance (EPR) spectrum confirms that the Cu II cation has an axial coordination symmetry and that the unpaired electrons occupy the d orbital. In addition, magnetic investigations showed that antiferromagnetic interactions exist in the Cu II atoms through the diamagnetic [Ni(CN)4 ] 2− ion.